Designing PAI-Based Digital LKPD: A Needs Study to Improve Spiritual Intelligence in Elementary School - Maida, Nur; Muhith, Abd; Gunawan (ATTA`DIB, 2025)
This study examines the need for developing a PAI-based digital LKPD to enhance spiritual intelligence among elementary school students at SDN 1 Ubung. Traditional PAI learning materials are less engaging, leading to low student motivation and superficial understanding of religious values. The research adopts a qualitative approach, involving interviews, observations, and document analysis. The findings reveal four key issues: (1) lack of interactive features in conventional PAI learning, (2) absence of reflection-based activities, (3) teachers' challenges in integrating technology, and (4) limited accessibility due to internet constraints. This study supports Keller’s ARCS Model, Bloom’s Taxonomy, and Zohar & Marshall’s Spiritual Intelligence Theory, emphasizing interactive, reflective, and accessible learning. The findings suggest that a well-designed digital LKPD can enhance student engagement, critical thinking, and moral development. Future research should explore long-term impacts and effective teacher training strategies for digital Islamic education.